2006
DOI: 10.1200/jco.2005.05.4163
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Chemoradiotherapy Compared With Radiotherapy Alone After Induction Chemotherapy in Inoperable Stage IIIA or IIIB Non–Small-Cell Lung Cancer: Study CTRT99/97 by the Bronchial Carcinoma Therapy Group

Abstract: Induction chemotherapy followed by chemoradiotherapy with weekly paclitaxel is feasible. Response, time to progression, and survival favor chemoradiotherapy compared with radiotherapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 19 publications
2
61
0
4
Order By: Relevance
“…Similar results were obtained for subgroup analysis of the five Phase-III trials. 15,19,20,21,37 Patterns of failure Pooling data of the initial relapse sites (Figure 2), difference between overall relapses (locoregional or distant) in both groups was statistically significant (OR ¼ 0.82; 95%CI: 0.69-0.97; p ¼ 0.02) in favor of concurrent group. Subset analyses revealed that isolated loco-regional relapses (primary tumor and/or regional nodes) were significantly lower frequent in the concurrent RT-CT than in the sequential arm (OR ¼ 0.68; 95%CI: 0.52-0.87; p ¼ 0.002), while the number of distant (e.g., brain, bone, or liver) relapses (OR ¼ 1.01; 95%CI: 0.79-1.30; p ¼ 0.927) and relapses at both sites (locoregional þ distant) (OR ¼ 0.74; 95%CI: 0.43-1.12; p ¼ 0.267) were similar in the two arms.…”
Section: Progression-free Survivalmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar results were obtained for subgroup analysis of the five Phase-III trials. 15,19,20,21,37 Patterns of failure Pooling data of the initial relapse sites (Figure 2), difference between overall relapses (locoregional or distant) in both groups was statistically significant (OR ¼ 0.82; 95%CI: 0.69-0.97; p ¼ 0.02) in favor of concurrent group. Subset analyses revealed that isolated loco-regional relapses (primary tumor and/or regional nodes) were significantly lower frequent in the concurrent RT-CT than in the sequential arm (OR ¼ 0.68; 95%CI: 0.52-0.87; p ¼ 0.002), while the number of distant (e.g., brain, bone, or liver) relapses (OR ¼ 1.01; 95%CI: 0.79-1.30; p ¼ 0.927) and relapses at both sites (locoregional þ distant) (OR ¼ 0.74; 95%CI: 0.43-1.12; p ¼ 0.267) were similar in the two arms.…”
Section: Progression-free Survivalmentioning
confidence: 97%
“…[15][16][17][18][19][20][21][22][23]37,38 Main characteristics of the 11 trials are described in Table 1. Of the 11 trials, 6 were randomized phase III trials, 15,16,[19][20][21]37 and the remaining 5 were randomized phase II trials. As of August 2009, 10 trials have already been published as full length articles and one was presented at the 2003 Annual Meeting of the ASCO.…”
Section: Trial Flow and Characteristics Of The Eligible Trialsmentioning
confidence: 99%
“…Five further trials were identified [13][14][15][16][17]; one of these was not considered in the meta-analysis because the sequential chemo-radiotherapy arm was stopped early after 19 patients and its results…”
Section: Meta-analysismentioning
confidence: 99%
“…The remaining 4 trials and the present study were divided in two sub-groups according to the timing of randomization: after induction in three trials [13][14][15] and before induction in two trials [16 and PITCAP trial].…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation